Theoretical Design of Novel Boron-Based Nanowires via Inverse Sandwich Clusters - Jiang, Cailian; Lv, Zhiwei; Lv, Sudong; Sai, Linwei; Wang, Shukai; Li, Fengyu (Frontiers in Chemistry, 2021)
Borophene has important application value, boron nanomaterials doped with transition metal have wondrous structures and chemical bonding. However, little attention was paid to the boron nanowires (NWs). Inspired by the novel metal boron clusters Ln2Bn− (Ln = La, Pr, Tb, n = 7−9) adopting inverse sandwich configuration [Li et al., 2018; Chen et al., 2019], we examined Sc2B8 and Y2B8 clusters in such novel structure and found that they are the global minima and show good stability. Thus, based on the novel structural moiety and first-principles calculations, we connected the inverse sandwich clusters into one-dimensional (1D) nanowires by sharing B−B bridges between adjacent clusters, and the 1D-Sc4B24 and 1D-Y2B12 were reached after structural relaxation. The two nanowires were identified to be stable in thermodynamical, dynamical and thermal aspects. Both nanowires are nonmagnetic, the 1D-Sc4B24 NW is a direct-bandgap semiconductor, while the 1D-Y2B12 NW shows metallic feature. Our theoretical results revealed that the inverse sandwich structure is the the most energy-favored configuration for transition metal borides Sc2B8 and Y2B8, and the inverse sandwich motif can be extended to 1D nanowires, providing useful guidance for designing novel boron-based nanowires with diverse electronic properties.